DNA oxidative damage in pregnant women upon exposure to conventional and alternative phthalates - Zhang, Ying-Jie; Wu, Liu-Hong; Wang, Fei; Liu, Liang-Ying; Zeng, Eddy Y.; Guo, Ying (Environment international, 2021)
[Display omitted] •Emerging plasticizer DPHP has entered the body of pregnant women in south China.•Levels of phthalate metabolites in pregnant women changed during pregnancy.•24% of women are exposure to higher levels of phthalates than the safety thresholds.•Closer correlations are found between conventional phthalates and 8-OHdG than the alternatives. Exposure to alternative phthalates and related health effects in pregnant women are rarely reported. Nineteen phthalate metabolites and a DNA oxidative damage biomarker 8-hydroxy-2′-deoxyguanosine (8-OHdG) were determined in urine samples of pregnant women recruited in South China. The detection frequencies and concentration of selected alternative phthalates, i.e., diisononyl phthalate (DiNP), diisodecyl phthalate (DiDP) and di-(2-propylheptyl) phthalate (DPHP) were lower than those of conventional phthalates. However, mono-(6-hydroxy-2-propylheptyl) phthalate, a metabolite of DPHP, was detected in 70% of urine samples (median: 0.13 ng/mL). The estimated daily intakes of conventional plasticizers, including dimethyl phthalate, di-n-butyl phthalate, diisobutyl phthalate and di-(2-ethylhexyl) phthalate (median range: 1.0–3.0 μg/kg_bw/day) were significantly higher than those of DiNP (0.08 μg/kg_bw/day) and DPHP (0.03 μg/kg_bw/day) (p < 0.05). Approximately 24% of pregnant women were at high risk when cumulative risk from exposure to several phthalates was considered. The concentrations of phthalate metabolites and urinary 8-OHdG were significantly correlated with each other (r = 0.206–0.772, p < 0.01), which were further conformed by multiple linear regression analysis (β = 0.168–0.639, p < 0.01). In addition, conventional phthalates were more strongly correlated with 8-OHdG than alternative phthalates (i.e., DiNP, DPHP), partly suggesting the relatively smaller health effects of alternatives due to their low exposure doses and toxicities. These findings suggested that alternative phthalates have entered the human body from consumer products in the study area, and exposure-related risk of DNA oxidative stress was comparatively lower.